Sonographic evaluation of the immediate effects of eccentric heel drop exercise on Achilles tendon and gastrocnemius muscle stiffness using shear wave elastography - Leung,Wilson K.C.; Chu,KL; Lai,Christopher (PeerJ, 2017)
Background Mechanical loading is crucial for muscle and tendon tissue remodeling. Eccentric heel drop exercise has been proven to be effective in the management of Achilles tendinopathy, yet its induced change in the mechanical property (i.e., stiffness) of the Achilles tendon (AT), medial and lateral gastrocnemius muscles (MG and LG) was unknown. Given that shear wave elastography has emerged as a powerful tool in assessing soft tissue stiffness with promising intra- and inter-operator reliability, the objective of this study was hence to characterize the stiffness of the AT, MG and LG in response to an acute bout of eccentric heel drop exercise. Methods Forty-five healthy young adults (36 males and nine females) performed 10 sets of 15-repetition heel drop exercise on their dominant leg with fully-extended knee, during which the AT and gastrocnemius muscles, but not soleus, were highly stretched. Before and immediately after the heel drop exercise, elastic moduli of the AT, MG and LG were measured by shear wave elastography. Results After the heel drop exercise, the stiffness of AT increased significantly by 41.8 + 33.5% (P < 0.001), whereas the increases in the MG and LG stiffness were found to be more drastic by 75 + 47.7% (P < 0.001) and 71.7 + 51.8% (P < 0.001), respectively. Regarding the AT, MG and LG stiffness measurements, the inter-operator reliability was 0.940, 0.987 and 0.986, and the intra-operator reliability was 0.916 to 0.978, 0.801 to 0.961 and 0.889 to 0.985, respectively. Discussion The gastrocnemius muscles were shown to bear larger mechanical loads than the AT during an acute bout of eccentric heel drop exercise. The findings from this pilot study shed some light on how and to what extent the AT and gastrocnemius muscles mechanically responds to an isolated set of heel drop exercise. Taken together, appropriate eccentric load might potentially benefit mechanical adaptations of the AT and gastrocnemius muscles in the rehabilitation of patients with Achilles tendinopathy.
Keywords: Heel drop exercise; Achilles tendon; Gastrocnemius muscle; Shear wave elastography; Mechanical adaptations